Science identity development: an interactionist approach - Ann Y. Kim; Gale M. Sinatra (SpringerOpen, 2018)
Abstract In this introduction for this Special Issue we discuss the need for the investigation of science identity with an emphasis on the environment. As such, we propose taking an interactionist approach; one that examines the person in interaction within their environment (Adams & Marshall, 1996). The Special Issue highlights the role of psychology constructs, such as interest and belonging that are deeply relevant and ultimately inform students' science identity development. The Special Issue includes six articles: this introduction, four empirical papers investigating the psychological experiences of students in various science spaces with a focus on the interactions between the individual and the context, and a commentary. Each contribution emphasized how the context either afforded or did not afford that sense of belonging to develop in students. The collection of articles were inspired by a symposium on the topic of STEM identity development that was presented at the 2017 annual meeting of the American Educational Research Association (AERA) in San Antonio, TX.